2008
DOI: 10.1590/s0100-879x2008005000047
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronotype and social zeitgebers on sleep/wake patterns

Abstract: Inter-individual differences in the phase of the endogenous circadian rhythms have been established. Individuals with early circadian phase are called morning types; those with late circadian phase are evening types. The Horne and Östberg Morningness-Eveningness Questionnaire (MEQ) is the most frequently used to assess individual chronotype. The distribution of MEQ scores is likely to be biased by several fact, ors, such as gender, age, genetic background, latitude, and social habits. The objective of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 30 publications
4
37
1
4
Order By: Relevance
“…Thus, in late chronotypes (evening types) sleep occurs in later hours, particularly on free days (Roenneberg et al 2003). On the other hand, during the workdays, evening individuals fall asleep much later than morning subjects do, but this difference shrinks (Roenneberg et al, 2003) or disappears (Korczak et al 2008) for waking up, as during workdays the rising time in most people is constrained by social duties (work, school etc.). This results in shortened sleep duration in late individuals during workdays (Zavada et al 2005;Korczak et al 2008); something they try to recover during free days by prolonging sleep (Zavada et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in late chronotypes (evening types) sleep occurs in later hours, particularly on free days (Roenneberg et al 2003). On the other hand, during the workdays, evening individuals fall asleep much later than morning subjects do, but this difference shrinks (Roenneberg et al, 2003) or disappears (Korczak et al 2008) for waking up, as during workdays the rising time in most people is constrained by social duties (work, school etc.). This results in shortened sleep duration in late individuals during workdays (Zavada et al 2005;Korczak et al 2008); something they try to recover during free days by prolonging sleep (Zavada et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…circadian pacemaker) and exogenous factors (e.g. work schedules and social commitments) in healthy adults (Kerkhof 1985), individuals with a relatively early circadian phase are morning-types and those with a relatively late circadian phase are evening-types (Korczak et al 2008). Morning and evening individuals differ in the phase of their endogenous circadian rhythms (Van Dongen 1998).…”
Section: Introductionmentioning
confidence: 99%
“…So, morning-types are phase advanced, showing a marked preference for waking at an early hour and find it difficult to remain awake beyond their usual bedtime, compared with evening-types, who show a preference for sleeping at later hours and often find it difficult to get up in the morning (Giannotti et al 2002). Because scores on self-report questionnaires measuring morning and evening chronotypes have been shown to correlate with differences in markers of the circadian pacemaker (Horne and Ostberg 1976;Smith et al 1989), an individual's chronotype is usually evaluated by a questionnaire (Korczak et al 2008). And, the aforementioned differences include the peak (Horne and Ostberg 1976), trough, amplitude (Baehr et al 2000), and period types (Duffy et al 2001) of the core-body temperature curve, as well as the melatonin (Griefahn 2002) and cortisol curves (Kudielka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although morning and evening types have different phases of sleep and wakefulness, some studies have showed that no chronotype differences in sleep duration, sleep latency, and sleep efficiency (Medeiros et al 2001;Mongrain et al 2006). Moreover, if evening types have sleep restriction due to school and work schedules as reported by much of the previous literature, they wake up very late on weekends to compensate for the sleep dept and would benefit the detoxification function of sleep (Korczak et al 2008;Borisenkov et al 2010).…”
Section: Discussionmentioning
confidence: 98%